Reaksi Pasar Terhadap Peristiwa Pemilihan Presiden Indonesia 2019 - Baskara, I Gede Aditya; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2019)
This research is an event study that aims to determine the market reaction arising from the 2019 Indonesian presidential election, against companies listed in the infrastructure stock sector on April 17, 2019, using the abnormal return indicator. This study uses secondary data in the form of daily stock prices per company during the period with the population of the infrastructure sector listed on the Indonesia Stock Exchange. The statistical tests used to test hypotheses are descriptive statistical tests, normality tests and one sample t-test. The results of the one sample t-test on abnormal return is that there is no significant difference, which means the market does not respond to the event. These results indicate that the efficient market is not answered in the 2019 Indonesian presidential election due to the absence of abnormal returns in it. Keywords : Event Study, Market Reaction, Abnormal Return, 2019 Indonesian Presidential Election.